Age-related ultrastructural changes in spheroids of the adipose-derived multipotent mesenchymal stromal cells from ovariectomized mice - Kyryk, Vitalii; Tsupykov, Oleg; Ustymenko, Alina; Smozhanik, Ekaterina; Govbakh, Iryna; Butenko, Gennadii; Skibo, Galyna (Frontiers in Cellular Neuroscience, 2023)
Adipose-derived multipotent mesenchymal stromal cells (ADSCs) are widely used for cell therapy, in particular for the treatment of diseases of the nervous system. An important issue is to predict the effectiveness and safety of such cell transplants, considering disorders of adipose tissue under age-related dysfunction of sex hormones production. The study aimed to investigate the ultrastructural characteristics of 3D spheroids formed by ADSCs of ovariectomized mice of different ages compared to age-matched controls. The female СВА/Са mice were randomly divided into four groups: CtrlY – control young (2 months) mice, CtrlO – control old (14 months) mice, OVxY – ovariectomized young mice, and OVxO – ovariectomized old mice of the same age. The electron microscopy analysis of spheroids from CtrlY animals revealed that ADSCs formed a culture of more or less homogeneous in size multicellular structures. The cytoplasm of these ADSCs had a granular appearance due to being rich in free ribosomes and polysomes, indicating active protein synthesis. Extended electron-dense mitochondria with a regular cristae structure and a predominant condensed matrix were observed in ADSCs from CtrlY group, which could indicate high respiratory activity. At the same time, ADSCs from CtrlO group formed a culture of heterogeneous in size spheroids. In ADSCs from CtrlO group, the mitochondrial population was heterogeneous, a significant part was represented by more round structures. This may indicate an increase in mitochondrial fission and/or an impairment of the fusion. Significantly fewer polysomes were observed in the cytoplasm of ADSCs from CtrlO group, indicating low protein synthetic activity. The cytoplasm of ADSCs in spheroids from old mice had significantly increased amounts of lipid droplets compared to cells obtained from young animals. Also, an increase in the number of lipid droplets in the cytoplasm of ADSCs was observed in both the group of young and old ovariectomized mice compared with control animals of the same age. Together, our data indicate the negative impact of aging on the ultrastructural characteristics of 3D spheroids formed by ADSCs. Our findings are particularly promising in the context of potential therapeutic applications of ADSCs for the treatment of diseases of the nervous system.